Tinjauan Hukum Terhadap Pidana Mati dalam Perspektif Hak Asasi Manusia - Putera, Airlangga; Jannah, Miftahul; Nasution, Hanry Setiawan (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to analyze the regulation of the death penalty in Indonesia and its implications for human rights. The method used in this study is library research with a normative approach and legal documentation. Regulations regarding the death penalty in Indonesia are regulated in the Criminal Code (KUHP) and in other sectoral laws. Based on statistical data and studies by criminologists, the death penalty is considered ineffective in reducing crime rates, because it does not provide a significant deterrent effect. On the other hand, the existence of the death penalty is considered contrary to the principles of human rights, especially the right to life. The right to life is a fundamental right guaranteed in various human rights instruments, such as the Universal Declaration of Human Rights, the International Covenant on Civil and Political Rights, the American Convention on Human Rights, Law Number 39 of 1999 on Human Rights, and the Charter of Fundamental Rights of the European Union. At the national level, the right to life is also constitutionally guaranteed in Article 28I paragraph (1) of the 1945 Constitution. In the perspective of Islamic law, the death penalty (qishash) was known before the advent of Islam and underwent reforms in its application in accordance with the principles of justice and protection of the soul. Therefore, the discourse on the sustainability of the death penalty in Indonesia needs to consider a comprehensive juridical, ethical, and theological approach.